INHIBITORY EFFECTS OF MANCOZEB ON GROWTH AND STIMULATION OF RESISTANCE AGAINST FUSARIUM WILT OF BRINJAL - NAZIYA, BANU; SHARADA, M. S. (The Bioscan, 2018)
Mancozeb was tested in four concentrations (0.05%, 0.10%, 0.15% and 0.20%) against Fusarium oxysporum f.sp. melongenae which causes destructive yield losses in brinjal. The results indicated that 0.20% showed maximum inhibition of 62.2% followed by 0.15% which recorded 57.7% inhibition. All the treatments were tested for seed germination and vigour studies at 3 h and 6 h in which 0.20% recorded maximum germination of 62% and vigour of 427.6 at 3 h whereas at 6 h it showed 58.6% germination and 387.6 seedling vigour. In control, poor germination of 44%, seedling vigour of 287.4 and 40.6% seed germination, vigour of 220.8 was observed at 3 h and 6 h respectively. All the treatments were analysed for vegetative growth, HR and disease protection studies and results stated that, the same 0.20% concentration was effective in increasing Plant height (8.4 cm), SFW (1.8 g), SDW (1g), RFW (1 g), RDW (0.6 g), HR (62%) and offered 51% protection in comparison to control and other treatments tested. Therefore, from the study it was concluded that, Mancozeb at 0.20% concentration was effective in inhibiting the pathogen growth, increased plant growth, HR and offered considerable protection in in vitro and green house studies.